Reduction of cardiovascular risk in professionals from a specialized health institute by a cardiovascular preventive program - Fernández Coronado, Rosalía Ofelia (2020)
Introduction. The cardiovascular rehabilitation programs (CRP) represent an effective multidisciplinary medical-health strategy in prevention and control of cardiovascular problems. Objective. To assess the impact of a CRP carried out in the workplace, in reducing absolute cardiovascular risk in INCOR workers. Methods. An experimental study. 41 workers with different levels of cardiovascular risk were included and were evaluated before and after their participation in the CRP on their functional capacity, cardiovascular risk factors and stress levels. The work intervention program consisted of 36 sessions of controlled physical activity, nutritional counseling, psychological counseling and laboratory evaluation. Results. The intervention get a reduction of the overall cardiovascular risk to the low level in all workers (100%), measured by the Framingham index and when it was measured with the ASCVD 2013 score, the high-risk level was eliminated and the intermediate level was reduced from 17,5% to 10%. The functional capacity shows an improvement, with an increase of cardiovascular risk level I from 19,5% to 90%. Blood lipids levels as VLDL, LDL, total cholesterol and triglycerides were significantly reduced in the post-intervention. Contrarily, in the HDL levels, the proportion of workers with non-recommended values increased to the end of the intervention. Finally, the CRP showed effectiveness in reducing workers’ stress. Conclusion: A CRP could to be implemented on workplace and it shows effectiveness in reducing cardiovascular risk and stress.